Blue surface-emitting distributed feedback lasers based on a high-mobility semiconducting polymer - Choulis, Stelios A.; Heliotis, George; Stavrinou, Paul N. (My University, 2005)
A detailed study of the charge transport and lasing properties of a novel blue emitting fluorene-based polymer, namely the Dow proprietary BP156 is reported
Keywords: Polymers; Semiconductor lasers; organic semiconductors